En bloc versus branched graft technique for supra-aortic vessel reimplantation in total arch replacement: a systematic review and meta-analysis - Kristine Santos; Kensei Oya; Tulio Caldonazo; Tomasz Płonek (Journal of Cardiothoracic Surgery, 2025)
Abstract Objectives Total arch replacement (TAR) necessitates reimplantation of supra-aortic vessels to preserve blood flow to the brain and upper body. En bloc (EB) or branched graft (BG) techniques are commonly performed for this, however, their comparative superiority remains under debate. Our meta-analysis aims to compare the outcomes associated with these two approaches. Methods A comprehensive literature search was performed across MEDLINE, Cochrane, and Scopus databases, focusing on studies that compared EB and BG for TAR. Pooled odds ratios (OR) and mean differences (MD) with 95% confidence intervals (CI) were calculated using RevMan 8.13.0. Results The final analysis included six observational studies comprising a total of 2,028 patients, with 50.2% of supra-aortic vessel reimplantations for TAR conducted using the EB technique. The pooled results revealed a statistically significant reduction in aortic cross-clamp (ACC) time favouring the EB group [MD -13.2 min; 95% CI -22.7 to -3.7; p < 0.05]. Intraoperative and 30-day mortality as well as other postoperative complications such as permanent and transient neurological deficits, acute kidney injury, myocardial infarction, reoperation for bleeding, and aortic reintervention were comparable between the two approaches. Conclusion The available evidence suggests that the EB technique is associated with a significantly shorter ACC time compared to the BG technique, with comparable rates of mortality and postoperative complications. However, these findings are limited by the observational nature of the included studies, therefore, higher-quality prospective research is needed to confirm our results.